2009
DOI: 10.1179/175158309x12560424605079
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamic characteristics of finite exponential film shaped slider bearings lubricated with micropolar fluid

Abstract: In this paper, the general dynamic Reynolds equation of sliding-squeezing surfaces of exponential shaped slider bearings with micropolar fluid is solved numerically for the assessment of dynamic characteristics. The two Reynolds type equations governing the steady performance and the perturbed characteristics are obtained using the perturbation technique and are solved numerically using the finite difference method. The results are compared with that of the inclined plane slider bearing. It is found that the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Dynamic characteristics of plane slider bearings were studied by Lin [18] in the presence of magnetic field and concluded that the applied magnetic field increases the dynamic coefficients. Static and dynamic characteristics of exponential bearing in presence of micropolar fluid were studied by Naduvinamani and Patil [19]. Recently, static and dynamic characteristics of parabolic and plane slider bearings lubricated with couple stress fluid in the presence of applied magnetic field studied by Naduvinamani et al [20].…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic characteristics of plane slider bearings were studied by Lin [18] in the presence of magnetic field and concluded that the applied magnetic field increases the dynamic coefficients. Static and dynamic characteristics of exponential bearing in presence of micropolar fluid were studied by Naduvinamani and Patil [19]. Recently, static and dynamic characteristics of parabolic and plane slider bearings lubricated with couple stress fluid in the presence of applied magnetic field studied by Naduvinamani et al [20].…”
Section: Introductionmentioning
confidence: 99%
“…Naduvinamani and Marali [15] derived the dynamic Reynolds equation for micropolar fluid lubrication of porous slider bearings. Later, Naduvinamani and Patil [16] derived the general dynamic Reynolds equation of exponential shaped slider bearing lubricated with micropolar fluid. Recently researchers are interested in the study of the surface roughness Japanese Society of Tribologists (http://www.tribology.jp/) N. B. Naduvinamani and Ashwini Angadi effects on bearings as the surface roughness is inherent in the process used for their manufacture.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of couple stress fluid on the dynamic characteristics of wide exponential-shaped slider bearings and wide Rayleigh step slider bearings was presented by Lin et al [28,29]. Naduvinamani and Patil [30] derived the dynamic Reynolds equation for micropolar fluid to study the dynamic characteristics of a finite exponential-shaped slider bearing. Singh and Gupta [31] theoretically investigated the effect of ferrofluid using the shliomis model on the dynamic characteristics of curved slider bearings.…”
Section: Introductionmentioning
confidence: 99%